2019
DOI: 10.1029/2019gl082464
|View full text |Cite
|
Sign up to set email alerts
|

81Kr Dating at the Guliya Ice Cap, Tibetan Plateau

Abstract: We present radiometric 81Kr dating results for ice samples collected at the outlets of the Guliya ice cap in the western Kunlun Mountains of the Tibetan Plateau. This first application of 81Kr dating on midlatitude glacier ice was made possible by recent advances in Atom Trap Trace Analysis, particularly a reduction in the required sample size down to 1 μL STP of krypton. Eight ice blocks were sampled from the bottom of the glacier at three different sites along the southern edges. The 81Kr data yield upper ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
1
15
1
1
Order By: Relevance
“…中低纬度山地冰川雪冰中左旋葡聚糖含量在 1 ng g -1 数量级 [24,63,65,66,68] ,比 南北极地区要高 1-2 个数量级 [64,67,72,73] 。位于高原南部希夏邦马峰南坡尼泊尔的 雅拉冰川,植被火燃烧烟尘能够被山谷风携带传输至高海拔冰川覆盖区,使雅拉 冰川雪冰中左旋葡聚糖含量较之希夏邦马峰北坡的达索普冰川高 2-3 个数量级 将现代冰芯记录与卫星遥感资料对比发现(图 5) ,左旋葡聚糖记录能够很 好的反映年际尺度的植被火燃烧变化 [44] ,冰芯中左旋葡聚糖含量峰值也能在一 定程度上反映植被火燃烧事件 [63,66,73] ,为利用冰芯左旋葡聚糖记录研究植被火燃 烧变化历史提供了理论基础 [63,69] 。 如利用青藏高原藏色岗日冰芯左旋葡聚糖记录 揭示了喜马拉雅山沿线地区在 21 世纪初期森林火灾等火燃烧快速增强 [44] 。 南极 Taylor Dome 冰芯和格陵兰 NEEM 冰芯左旋葡聚糖记录都揭示了全新 世以来植被火燃烧逐渐增强的趋势 [62,72] ;火燃烧在大约 2-3 ka BP 达到峰值,随 后逐渐减弱,这与炭屑记录反演的火燃烧变化是基本一致的 [72] ,可能与同期全 球人类用火开垦荒地等活动增强有关 [1,72,94] ;而 NEEM 冰芯中左旋葡聚糖极值事 件在近 2000 年也更频繁出现 [73] 。在南极 Dome C 冰芯中,冰期样品中左旋葡聚 糖含量高于间冰期样品 [75] ,可能反映了南半球冰期-间冰期的植被火燃烧变化规 律。但南北极地区远离植被火燃烧源,冰芯样品中左旋葡聚糖含量比青藏高原为 代表的中低纬度地区低 2-3 个数量级 [24,62,72,73] ,且不连续取样可能会造成一些记 录信息丢失 [8] 。近年来,借助原子阱单原子检测定年方法,发现青藏高原古里雅 冰帽等年代可超过 74 ka BP [95] ,在古里雅冰帽海拔 6700 米处获取的冰芯底部样 品中也检测到了较高的左旋葡聚糖含量(约 2 ng g -1 ,未发表) ,有望为理解亚洲 等中低纬度地区冰期-间冰期尺度的植被火燃烧变化提供高分辨率证据。…”
Section: 雪冰中的左旋葡聚糖unclassified
“…中低纬度山地冰川雪冰中左旋葡聚糖含量在 1 ng g -1 数量级 [24,63,65,66,68] ,比 南北极地区要高 1-2 个数量级 [64,67,72,73] 。位于高原南部希夏邦马峰南坡尼泊尔的 雅拉冰川,植被火燃烧烟尘能够被山谷风携带传输至高海拔冰川覆盖区,使雅拉 冰川雪冰中左旋葡聚糖含量较之希夏邦马峰北坡的达索普冰川高 2-3 个数量级 将现代冰芯记录与卫星遥感资料对比发现(图 5) ,左旋葡聚糖记录能够很 好的反映年际尺度的植被火燃烧变化 [44] ,冰芯中左旋葡聚糖含量峰值也能在一 定程度上反映植被火燃烧事件 [63,66,73] ,为利用冰芯左旋葡聚糖记录研究植被火燃 烧变化历史提供了理论基础 [63,69] 。 如利用青藏高原藏色岗日冰芯左旋葡聚糖记录 揭示了喜马拉雅山沿线地区在 21 世纪初期森林火灾等火燃烧快速增强 [44] 。 南极 Taylor Dome 冰芯和格陵兰 NEEM 冰芯左旋葡聚糖记录都揭示了全新 世以来植被火燃烧逐渐增强的趋势 [62,72] ;火燃烧在大约 2-3 ka BP 达到峰值,随 后逐渐减弱,这与炭屑记录反演的火燃烧变化是基本一致的 [72] ,可能与同期全 球人类用火开垦荒地等活动增强有关 [1,72,94] ;而 NEEM 冰芯中左旋葡聚糖极值事 件在近 2000 年也更频繁出现 [73] 。在南极 Dome C 冰芯中,冰期样品中左旋葡聚 糖含量高于间冰期样品 [75] ,可能反映了南半球冰期-间冰期的植被火燃烧变化规 律。但南北极地区远离植被火燃烧源,冰芯样品中左旋葡聚糖含量比青藏高原为 代表的中低纬度地区低 2-3 个数量级 [24,62,72,73] ,且不连续取样可能会造成一些记 录信息丢失 [8] 。近年来,借助原子阱单原子检测定年方法,发现青藏高原古里雅 冰帽等年代可超过 74 ka BP [95] ,在古里雅冰帽海拔 6700 米处获取的冰芯底部样 品中也检测到了较高的左旋葡聚糖含量(约 2 ng g -1 ,未发表) ,有望为理解亚洲 等中低纬度地区冰期-间冰期尺度的植被火燃烧变化提供高分辨率证据。…”
Section: 雪冰中的左旋葡聚糖unclassified
“…The released gas was collected in containers and shipped to USTC for Kr purification and 81 Kr analysis using Atom Trap Trace Analysis (ATTA). The extraction procedure was described in detail by Tian et al (2019), and the principle of ATTA was described by Jiang et al (2012).…”
Section: Kr Datingmentioning
confidence: 99%
“…A successful method for dating blue ice is to correlate globally well-mixed atmospheric gas records (e.g., CH4, CO2, δ 18 Oatm) and glaciochemical records (e.g., nss-Ca 2+ , δ 18 Oice, δ 2 Hice) with existing well-dated ice core records (Spaulding et al, 2013;Baggenstos et al, 2017;Baggenstos et al, 2018;Menking et al, 2019). Other effective methods include the use of stable Ar isotopes (Higgins et al, 2015;Yau et al, 2015;Yan et al, 2019) or the radioactive 81 Kr (Loosli&Oeschger 1969;Tian et al, 2019;Crotti et al, 2021), which both provide independent and absolute age constraints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, at that time, 10 5 -10 6 kg of ice was required. In virtue of developing Atom Trace Trap Analysis (ATTA), the required ice has kept decreasing (Lu et al, 2014;Tian et al 2019;Jiang et al, 2020;Crotti et al, 2021). Buizert et al (2014) for the first time, showed that 81 Kr age dating is feasible for blue ice in Taylor Glacier, Antarctica.…”
mentioning
confidence: 99%